Effects of Transducer Placement on Load–Velocity Relationships in Smith Machine and Free Weight Squats in Trained Women - Athanasios Tsoukos; Gregory C. Bogdanis (Journal of Functional Morphology and Kinesiology)
Background: We examined the effects of linear position transducer placement during Smith machine (SM) and free weight (FW) full squats on the mean velocity and the load–velocity relationship in trained women. In addition, we examined the relationship between the load–velocity characteristics and jump performance, to determine which testing approach is more appropriate for both the testing and transfer of training effects. Methods: Eleven trained women were assessed for 1-RM in FW and SM full back squats. Linear position transducers (LPTs) were attached to the barbell (BAR) and to the belt (BELT) during FW and SM full back squats. The mean velocity was measured across progressively increasing loads (30–100%). The load–velocity relationships were modeled using linear regression, and the velocity values, as well as the load–velocity parameters, were compared across all conditions (SM BAR, SM BELT, FW BAR, and FW BELT). Squat jump, countermovement jump, and drop jump performance were also assessed using an optical measurement system. Results: In SM compared to FW, 1-RM was higher (92.9 ± 16.2 kg vs. 85.1 ± 14.5 kg, p < 0.05, d = 0.53). A strong agreement was observed between the FW BAR and FW BELT (Lin’s concordance correlation coefficient CCC = 0.96–0.99), as well as between the SM BAR and FW BAR (CCC = 0.95–0.97) at low-to-moderate intensities (30–70% 1-RM), suggesting that these conditions can be used interchangeably. However, the SM BELT systematically showed lower mean velocity values at 30–80% 1-RM and exhibited low agreement across all other conditions. In contrast, the FW BELT mean velocity was lower than that of the FW BAR and SM BAR only at higher intensities (>80% 1-RM). V0 and mean velocities at low-to-moderate loads (30–70% 1-RM) showed strong correlations with all jump types, with relationships gradually weakening as the load increased (r = 0.63–0.93, p < 0.05). The highest correlations were observed in the SM BAR and FW BELT conditions. Lastly, the relative strength demonstrated a consistent relationship with squat jump and drop jump performance exclusively in the FW condition (r = 0.71 and 0.72, p < 0.05). Conclusions: The FW BAR and FW BELT showed strong agreement at submaximal loads and may be used interchangeably, while the SM BELT showed a lower mean velocity and low agreement with other conditions. The load–velocity relationship parameters and mean velocity at low-to-moderate loads correlated strongly with the jump performance. Coaches and practitioners can use bar-mounted and belt-mounted LPTs interchangeably during FW squats for velocity-based training at submaximal intensities when working with trained women. Additionally, tracking the mean velocity at low-to-moderate loads provides valuable insights into lower-body explosive performance, supporting more precise and individualized training prescriptions and performance monitoring.